(untitled) (LIS TODAY, 2025)
Purpose: The increasing use of electronic resources (e-resources) has transformed the landscape of academic research and knowledge dissemination and it has become necessary for library professionals to study its utility. The aim of this study is to examine the awareness and usage of e-resources among research scholars in the Faculty of Social Sciences in universities of the state of Bihar. Methodology: This study employed a mixed-methods approach, consisting of a survey and semi-structured interviews, to collect data from a sample of 110 research scholars from various social science disciplines across five government universities in the state of Bihar. Findings: The findings indicate that the level of awareness about e-resources among research scholars is very high, and most respondents regularly use these resources for their research work. However, the study also highlights the need for better access, training and institutional support to further improve the effective use of e-resources. The findings reveal a significant correlation between awareness levels and the effective use of e-resources, highlighting the need for improved training and access. Originality: This is the first research of its kind on the use and awareness of e-resources by research scholars of the Faculty of Social Sciences of universities in Bihar. These results provide valuable insights for academic institutions in Bihar to develop targeted strategies and policies that promote the integration of e-resources in the research and academic activities of their stakeholders.